Minority rights in the Pacific region a comparative analysis - Castellino, Joshua; Keane, David, 1978- (Oxford : Oxford University Press, 2009)
The Pacific region has often been ignored in the literature examining the protection of minority rights. This text advances the understanding of vulnerable groups across the region through a comparative analysis of the theory and practice of minority rights law in states such as Fiji, Papua New Guinea, Australia and New Zealand.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Minorities -- Legal status, laws, etc. -- Oceania; Human rights -- Oceania